2008
DOI: 10.1002/bit.21661
|View full text |Cite
|
Sign up to set email alerts
|

Lab‐scale fermentation tests of microchip with integrated electrochemical sensors for pH, temperature, dissolved oxygen and viable biomass concentration

Abstract: This article shows the development and testing of a microchip with integrated electrochemical sensors for measurement of pH, temperature, dissolved oxygen and viable biomass concentration under yeast cultivation conditions. Measurements were done both under dynamic batch conditions as well as under prolonged continuous cultivation conditions. The response of the sensors compared well with conventional measurement techniques. The biomass sensor was based on impedance spectroscopy. The results of the biomass sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 36 publications
0
57
0
Order By: Relevance
“…Controlling pH may also be important, as it has been demonstrated that small changes, up or down, in the pH of the medium provided to ES cells results in an approximately 50% decrease in the yield of cells capable of forming embryoid bodies (three dimensional spheroids of differentiating ES cells) (83). Ultimately, it is likely that control of oxygen and pH in artificial stem cell niches will require new sensor technologies, capable of cell-level measurement and control (84), enabling prospectively controllable links between cell signaling, gene regulation, and metabolic networks (85).…”
Section: Ecm Microarraysmentioning
confidence: 99%
“…Controlling pH may also be important, as it has been demonstrated that small changes, up or down, in the pH of the medium provided to ES cells results in an approximately 50% decrease in the yield of cells capable of forming embryoid bodies (three dimensional spheroids of differentiating ES cells) (83). Ultimately, it is likely that control of oxygen and pH in artificial stem cell niches will require new sensor technologies, capable of cell-level measurement and control (84), enabling prospectively controllable links between cell signaling, gene regulation, and metabolic networks (85).…”
Section: Ecm Microarraysmentioning
confidence: 99%
“…Recently, an integrated sensor array has been developed, based on the 96-well microtiter plate format, containing sensors for pH, dissolved oxygen, temperature, and viable biomass concentration. 22,23 Compatibility of a miniaturized bioreactor system to the current high-throughput cell cultivation platforms, i.e. the 24 and 96 (deep)well plates, is highly desirable because of the already available automation equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Taking this into account, we developed a parallelized micro bioreactor system with a working volume of 100 lL based on the 96-well microtiter plate format. In each of the micro bioreactors, a recently developed electrochemical sensor array 22,23 was integrated for the online measurement of temperature, pH, dissolved oxygen concentration, and viable biomass concentration. The cumulative CO 2 production during the cultivations was measured with a conductometric sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the pH-control and fed-batch fermentations could be performed by feedback controlling the opening times of the acid or base microvalve or establishing glucose pulses in response to an increasing DOT. Besides some attempts to measure pH, DOT, and biomass with electronic sensors (Krommenhoek et al, 2008), the common method to monitor the important fermentation parameters in the described microbioreactors is the non-invasive, optical measurement by means of optodes (pH and DOT) or light transmission (OD).…”
Section: Introductionmentioning
confidence: 99%